'God save Antonio Fradeletto': Anglophilia and the consumption of British Art at the Venice Biennale, 1895–1914. Issue 4 (8th August 2021) - Tavinor, Marie
ABSTRACT: The literature generally hails Antonio Fradeletto (1858-1930), first general secretary of the Biennale between 1895 and 1914, as instrumental in organising the venture and in setting forth its artistic and commercial direction in conjunction with the City Mayor, president of the Biennale. During these early 'heroic' years of the Biennale, the general secretary concentrated a lot of power in his hands, from curating some of the sections, to managing the venue, to facilitating the sales. In addition, Fradeletto was an elected MP representing Venice at the Parliament in Rome, who also found the time to pursue some intellectual and literary activities. Antonio Fradeletto is therefore taken as an 'ego-centric' case study to explore the extent and limits of agency at the Venice Biennale. Indeed, by focussing specifically on Fradeletto's acknowledged Anglophilia and on his support of the British section, this article seeks to highlight the negotiations and compromises going on behind the scene, and the way Fradeletto pushed his own preferences to implement his vision of the Biennale. More broadly, this perspective allows to investigate how far political and cultural biases may affect the development of a cultural institution such as the Biennale.